Factors Determining the Acceptance of E-Wallet among Gen Z from the Lens of the Extended Technology Acceptance Model - Rosli, Mohd Shafie; Saleh, Nor Shela; Md. Ali, Azlah; Abu Bakar, Suaibah (Mdpi, 2023)
: E-wallets are one of the breakthroughs brought forth by the evolution of FinTech, which has been accentuated by the global outbreak of COVID-19. Therefore, it is critical to comprehend the factor of e-wallet acceptance. As this technology advances, substantial knowledge and research gaps become apparent. Previous studies on e-wallet acceptance have overlooked the importance of motivation and self-efficacy. There is a dearth of focus on certain age groups, such as Gen Z, which is currently the trendsetter of new technologies. This study aims to close the gaps regarding the lack of focus toward Gen Z, motivation, and self-efficacy in understanding e-wallet acceptance by combining the Technology Acceptance Model (TAM) with Self-Determination Theory (SDT), Self-Efficacy (SE), and Digital Media Self-Efficacy (DMSE) to fully understand the factors influencing e-wallet acceptance among Gen Z, using 233 samples to test 16 hypotheses derived from the identified research and knowledge gaps. External Regulation (ER), SE, and DMSE are the determinants of acceptance, according to Structural Equation Model analysis conducted. Mediation analysis reveals that Attitude toward Use (AT) is the full mediator of Perceived Usefulness (PU) and Perceived Ease of Use (PEU). The quintessential outcome of this research is the Model of E-Wallet Acceptance among Gen Z, which is significant for FinTech industries looking to strategically roll out e-wallet initiatives as well as a point of exploration for numerous future academic research and development.